Applications of intrinsic safety characteristic parameters of propellant dust: Commercial multi-tube pyrotechnic hazard assessment. (March 2021) - Zhao, Jue-Quan; Cheng, Yu-Chi; Hou, Hung-Yi; Chen, Wei-Chun
Abstract: Fireworks are widely used in festivals around the world, but the safety issue during preparation the manufacture, storage, and operation of pyrotechnics has also been highly valued. Human operation error and insufficient recognition of the safety characteristics of pyrotechnics are the main factors in pyrotechnic incidents in Taiwan. This study considers thermal and explosion safety by electrostatic sensitivity, minimum ignition temperature, and explosion characteristics of propellant dust in commercial multi-tube pyrotechnics. The results show that propellant dust is not sensitive to static electricity, but it was ignited at 260 °C environment temperature. The lower explosion limit of propellant dust was 125–150 g/m 3, which provided an effective control of the dust concentration in the workplace. It was also found that the explosive level of the propellant dust belonged to St-1, which is exceptionally close to St-2 explosion influence, and that cannot be ignored. The high temperature associated with the explosion reminded that after the firework is launched, it should be cooled before leaving. Combining the above results, this research suggests the environmental operation temperature and dust concentration should be controlled within a safer range to effectively avoid the occurrence of dust fire or explosion and substantially enhance the safety of the pyrotechnic industry. Highlights: Human error and insufficient recognition are the main factors in pyrotechnic incidents in Taiwan. Propellant dust is not sensitive to static electricity, but it was ignited at 260 °C. The explosive level of the propellant dust belonged to St-1 (close to St-2). The high temperature associated with the explosion reminded that after the firework is launched. Environmental temperature and dust concentration should be controlled within a safer range.